Analysis Of Patient Satisfaction With The Implementation Of Bedside Handover In The Inpatient Ward Of Eka Hospital PIK - Sari, Maya (Jurnal Kesehatan, 2026)
Introduction: Effective clinical communication is a critical determinant of patient safety and satisfaction in healthcare services. Bedside handover, a structured communication process conducted at the patient’s bedside, is widely recommended to support patient-centered care. However, its implementation remains inconsistent, particularly in private hospital settings. This study aimed to analyze the relationship between bedside handover implementation and patient satisfaction in Eka Hospital PIK. Method: This study employed an analytical observational design with a cross-sectional approach. A total of 60 inpatients were selected using a total sampling technique. Data were collected using a bedside handover observation checklist based on SBAR standards and a modified version of the Newcastle Satisfaction with Nursing Scale (NSNS). Data were analyzed using the Chi-square test with a significance level of p < 0.05. Results: The majority of bedside handover practices were categorized as good (56.7%), while patient satisfaction levels were predominantly high (61.7%). Statistical analysis revealed a significant relationship between bedside handover implementation and patient satisfaction (p = 0.002). Conclusion: Bedside handover has a significant influence on patient satisfaction. Strengthening communication quality and enhancing patient involvement are essential strategies to improve healthcare service outcomes.